Climate change, agriculture and international migration: An African youth perspective - Bezu, Sosina; Demissie, Teferi Dejene; Abebaw, Degnet; Mungai, Catherine; Kassa, Habtemariam; Huyer, Sophia; Solomon, Dawit (2019)
Existing evidence indicates that Africa is already being affected by climate change resulting in substantial challenges for both human and natural systems. Eastern Africa is among the regions in Africa with disproportionately higher risk of adverse consequences of global warming and climate change. Climate change and variability are having significant direct and indirect impacts on agricultural production, agricultural value chains, food and nutrition security as well as the overall sustainable growth of the sector in the region. Over time, it is expected that climate change will exacerbate the prevalence of spatio-temporal climate variability in Eastern Africa, and these variabilities will manifest in the increased frequency and severity of extreme climate events and the increasing irregularity and unpredictability of weather patterns. To the region’s farmers, these emerging changes represent an additional source of risks and uncertainty.